Urgensi Pelaporan Gratifikasi dan Konsekuensi Hukum bagi Penyelenggara Negara - Mahmud, Ade (Ajudikasi : Jurnal Ilmu Hukum, 2024)
The practice of gratification is for the Indonesian people a natural and natural tradition, but if the gift has a power relationship related to the duties and positions of the recipient, the meaning of the gift is no longer considered normal and leads to corrupt behavior. This writing aims to determine the criteria for gratification offenses that are considered bribes and determine the implications of gratification reporting. This research using normatif approach by identification regulation of gratification, technic collection data using library research by qualitative analysis. Gratification is considered corruption if it is given in connection with the recipient's duties and authority as a state administrator and is not reported to the Corruption Eradication Commission. The legal consequences of reporting gratuities for civil servants are that they are free from criminal threats, free from conflicts of interest, reflect high integrity, and are a means of self-evaluation.